Effect of internal void placement on the heat transfer performance – Encapsulated phase change material for energy storage. (June 2015) - Solomon, Laura; Elmozughi, Ali F.; Oztekin, Alparslan; Neti, Sudhakar
Abstract: The effect of an internal air void on the heat transfer phenomenon within encapsulated phase change material (EPCM) is examined. Heat transfer simulations are conducted on a two dimensional cylindrical capsule using sodium nitrate as the high temperature phase change material (PCM). The effects of thermal expansion of the PCM and the buoyancy driven convection within the fluid media are considered in the present thermal analysis. The melting time of three different initial locations of an internal 20% air void within the EPCM capsule are compared. Latent heat is stored within an EPCM capsule, in addition to sensible heat storage. In general, the solid/liquid interface propagates radially inward during the melting process. The shape of the solid liquid interface as well as the rate at which it moves is affected by the location of the internal air void. The case of an initial void located at the center of the EPCM capsule has the highest heat transfer rate and thus fastest melting time. An EPCM capsule with a void located at the top has the longest melting time. Since the inclusion of a void space is necessary to accommodate the thermal expansion of a PCM upon melting, understanding its effect on the heat transfer within an EPCM capsule is necessary. Highlights: High temperature phase change materials for thermal energy storage. Both the enthalpy–porosity and volume of fluid methods have been employed. EPCM capsule designed with a 20% void with different void configurations. Comparison of different initial void locations on the heat transfer in the EPCM. The location of the void has a profound effect on the melting time.